Biogeophysical and Biogeochemical Processes at the Surface Determine Habitability in Two Extreme Climates - Shum, Greta Enid Marie (My University, 2024)
In this dissertation we make two habitability assessments of Earth's climate. We examine first the habitability of Snowball Earth and second the habitability of Earth's future climate under different rates of decarbonization. In both cases, the concept of habitability can initially be seen as an interdisciplinary link between climate science and other fields; in using this metric, we gain insight into water-based life on Earth and on other worlds as well as mitigation policy. At a deeper level in both cases, habitability serves as a guiding light to illuminate other physical climate insights, in particular the power of biogeophysical and biogeochemical surface processes that couple the atmosphere, land, and ocean in regulating Earth's climate. Because these "surface-level" processes elicit responses across various components of the climate system, they have an strong influence on climate feedbacks and, as a result, the resilience or sensitivity of Earth's climate to extreme radiative changes. In Chapter 2, we examine the influence of land surface albedo on habitability as it concerns eukaryotic, photosynthetic algae. We find that by regulating the flux of energy to the Earth system and, by extension, regulating the potential flux of water to the atmosphere, bare land surface albedo exerts a stronger control on habitability of likely refugia than the radiative influence of CO2 concentration. In Chapters 3 and 4, we investigate how the cycling of carbon among the atmosphere, land, and ocean, as determined explicitly by carbon cycle model structure and implicit model assumptions about how carbon is fluxed across carbon pools, influences the habitability of future Earth for human populations. In Chapter 3 we examine four simple climate models that represent the terrestrial and ocean carbon cycles differently. We test the models' responses to a variety of increasing and decreasing CO2 emissions and find that the models behave similarly in an increasing-emissions regime and diverge in their response to decreasing emissions. We quantify how those differences in response to decarbonization change implied necessary mitigation policy through changes to the Remaining Carbon Budget. In Chapter 4, we explore which aspects of modeled global biogeochemistry exert the strongest influence on the climate response to decarbonization. To do this, we compare two representations of the carbon cycle, selected from Chapter 3's intercomparison, and perform a comparison using a set of perturbed parameter ensembles. We find that differences in carbon cycle model structure lead to differences in the long-term carbon sinks but do not explain differences in climate response to decarbonization. This disconnect between carbon cycle modeling choices and climate response reflects a structural disconnect between carbon cycling and energy balance. To account for the role ocean circulation plays in both systems, we add a link between the two components and consequently change the coupling within the energy balance component and the carbon cycle component. This structural connection assumes different trade-offs in the observed carbon-climate system, leading to different behavior both in an increasing-emissions and decreasing emissions regime. In particular, when we assume that exchange of heat to the deep ocean is linked to ocean circulation and thus the oceanic uptake of carbon, we find that in order to match present day observations of temperature and CO2 the climate must warm more per unit of forcing, resulting in a smaller remaining carbon budget. These insights refine our understanding of how the atmosphere, biosphere, and hydrosphere are connected and have important consequences for how we represent their coupling in complex and simple climate models for other applications.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Atmospheric sciences; Climate change; Paleoclimate science; Atmospheric sciences